Increased acid sphingomyelinase activity in peripheral blood cells of acutely intoxicated patients with alcohol dependence - Reichel, Martin; Greiner, Elisabeth; Richter-Schmidinger, Tanja; Yedibela, Oezlem; Tripal, Philipp; Jacobi, Andrea; Bleich, Stefan; Gulbins, Erich; Kornhuber, Johannes (Alcoholism-Clinical and Experimental Research, 2010)
Background: Acid sphingomyelinase (ASM; EC 3.1.4.12) hydrolyses membrane sphingomyelin into the bioactive lipid ceramide and is thus involved in different cellular processes such as differentiation, immunity, or cell death. Activation of ASM has been reported in particular in conjunction with the cellular stress response to several external stimuli, and increased ASM activity was observed in a variety of human diseases. Ethanol-induced activation of ASM has been observed in different cell culture systems, thus raising the question about the effect of alcohol intoxication in human subjects on ASM activity in vivo. Methods: We determined ASM activity in peripheral blood mononucleated cells of 27 patients suffering from alcohol dependence. Patients were classified according to their blood alcohol concentration at admission, and ASM activity was determined repeatedly from all patients during alcohol withdrawal. Results: Acutely intoxicated patients displayed significantly higher ASM activity than patients in early abstinence (Mann-Whitney U test: Z = - 2.6, p = 0.009). ASM activity declined in acutely intoxicated patients to normal values with the transition from the intoxicated state to early abstinence (Wilcoxon test: Z = -2.7, p = 0.007). At the end of withdrawal, ASM activity was significantly increased again compared to the early phase of abstinence in both patient groups (Wilcoxon test: Z = -2.691, p = 0.007 and Z = -2.275, p = 0.023, respectively). Conclusions: Alcohol-induced activation of ASM occurs in human subjects and might be responsible for deleterious effects of ethanol intoxication. Chronic alcohol abuse may induce deregulation of sphingomyelin metabolism in general, and this impairment may cause side effects during withdrawal from alcohol. © 2009 by the Research Society on Alcoholism.
Created from Fastlane, Scopus look-up
Keywords: Alcohol Dependence; Ceramide; Sphingomyelin; Sphingomyelin Phosphodiesterase; Sphingomyelinase